The role of social ties in collaborative project networks: A tale of two construction cases. Issue 9 (2nd September 2021) - af Hällström, Anna; Bosch-Sijtsema, Petra; Poblete, León; Rempling, Rasmus; Karlsson, Mats
Abstract: Collaborative project delivery models (CPDMs) are increasing in popularity as infrastructure construction projects become more complex and grow in scale and scope. CPDMs build on high levels of trust, information exchange and formal contractual relations, creating complex relationships between actors in the project network. The literature emphasizes the procurement phase and contractual aspects of CPDMs; however, few studies explicitly focus on the role of social relationships in CPDM projects. Social network theory has recently been introduced in the architecture, engineering and construction industry industry to study relationships between network actors, but the role of social ties within CPDM project networks is still unclear. Through two qualitative case studies, we have analyzed the role of social ties in projects applying a CPDM contract. The empirical evidence of 41 semi-structured interviews and observations points to aspects that affect the development of social ties in CPDMs, such as initial project setup, project identification, perception of actors, resource sharing and shared space, as well as the importance of formal and informal ties for supporting collaborative project practices. The evidence shows how social ties develop into negative or positive bonds affecting the level of collaboration. This study contributes by emphasizing the interplay between project networks using CPDMs and social ties.